The Accreditation Council of Trinidad and Tobago (ACTT): Strategic Plan 2020 – 2025 (Abridged Version) - The Accreditation Council of Trinidad and Tobago (ACTT) (The Accreditation Council of Trinidad and Tobago (ACTT), 2020)
The Strategic Plan (2020-2025) is a formal document which articulates five years of focused capacity building actions. It is characterised by several components which include the vision statement, mission statement, core values, priorities, goals, key performance indicators, objectives and enabling and core actions that were developed during the organisation’s strategic planning exercise. This Strategic Plan is aligned to regional and national education policies. Benchmarking of strategies from similar external quality assurance bodies and systems, has resulted in the adoption of suitable approaches. A detailed SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis was also conducted. The SWOT analysis resulted in the identification of various strategic opportunities, which are articulated in the Strategic Plan. During this exercise, the Council engaged in an extensive research-based consultative approach by obtaining feedback from key stakeholders such as the Parliament; Government; registered and accredited PSTE institutions; international and regional agencies; external evaluators; existing and former staff and management of ACTT; and from members of former ACTT boards.
Keywords: Accreditation; Strategic plan; Post-secondary education; Tertiary education; PSTE